LAUMONIERA H.P. NOOTEBOOM (SIMAROUBACEAE) REDUCED TO BRUCE A J.F. MILL. - KOSTERMANS, A.J.G.H. (Research Center for Biology, 1988)
Comparison of all the collected material, together with the cursory description of Laumoniera Nooteboom, made it clear that the only difference with the genus Brucea is the shape of the stigma. This is not considered to be at the generic level and the genus is sunk into Brucea and the species renamed Brucea bruceadelpha (Nooteboom) Kostermans, comb, nov.